Undergraduate leadership experience and workplace stress management among alumni of International Islamic University Malaysia - Abdul Ghani, Radiah; Mohd. Nor, Muhammad Anwar; Mamat, Mohd. Nor; Mahamood, Siti Fatahiyah (USIM Press, 2025)
Despite increasing emphasis on graduate employability and mental well-being, limited research has examined how undergraduate leadership experiences influence stress management in the workplace. This study explores the relationship between student leadership involvement and workplace stress management among alumni of the International Islamic University Malaysia, incorporating an Islamic perspective that guides holistic well-being. Using a qualitative research approach, the study identified five major sources of workplace stress, eight mechanisms utilised by alumni to manage stress, and six transferable skills nurtured through leadership involvement that contribute to a positive work environment. Notably, many alumni highlighted the role of Islamic values such as tawakkul (reliance on Allah), sabr (patience), self-accountability, and ethical conduct in shaping their coping strategies and leadership behaviours. The findings reveal a meaningful association between undergraduate leadership experience and the ability to manage stress effectively in professional settings, supported by Islamic principles that promote emotional resilience and balanced living. These insights can guide the university in evaluating and enhancing the effectiveness of its ecosystem in nurturing graduates who are professionally competent and spiritually grounded.